The Effectiveness of STEAM Learning Model Implementation in Primary School Students' IPAS Learning: A Systematic Literature Review - Muntazah, Adinda; Elizar; Berta Apriza; Irawan Suprapto (Universitas Pendidikan Ganesha, 2025)
Learning in elementary schools still lacks innovative approaches that integrate various disciplines contextually. The STEAM model has the potential to be a solution, and this study aims to analyze its effectiveness in IPAS learning through a Systematic Literature Review (SLR) approach. Literature searches were conducted through the Google Scholar database with a phased approach. The first stage using the keyword “Learning Model” resulted in 314,000 documents. The addition of the keyword “STEAM” in the second stage narrowed the results to 6,640 documents. The third stage adding the keyword “IPAS” yielded 270 documents, while the fourth stage adding the keyword “Elementary School” filtered the results to 246 documents. After strict selection based on the inclusion criteria, 7 relevant articles were obtained for further analysis. The results showed that the STEAM model significantly improved students' critical thinking skills, higher order thinking skills and learning outcomes. In addition, this approach provides in-depth, relevant and contextualized learning experiences, supporting students' holistic development. The implication of this research is the importance of developing a curriculum that supports the systematic and consistent implementation of the STEAM model in primary schools. In addition, teacher training is needed to improve competence in implementing this approach in order to maximize its impact on learning quality. The STEAM model can also be the basis for developing educational policies that are oriented towards the demands of 21st century learning.